Changes in working conditions and subsequent sickness absence - Peppiina Saastamoinen; Mikko Laaksonen; Eero Lahelma; Tea Lallukka; Olli Pietiläinen; Ossi Rahkonen (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: The aim of the study was to examine the associations of changes in exposure to physical and psychosocial working conditions on subsequent sickness absence among ageing municipal employees of the City of Helsinki, Finland. METHODS: Changes in exposure to working conditions were assessed between baseline (2000-2002) and follow-up (2007) surveys. Register-based sickness absence information was linked to the survey data (N=3739) and followed-up from the return of the questionnaire in 2007 to the end of 2010. The study included six measures of physical and two measures of psychosocial working conditions. Negative binomial regression analysis was used to assess the associations and adjust for covariates. RESULTS: Favorable changes in physical working conditions lowered the risk for sickness absence whereas adverse changes increased the risk. Adverse changes in psychosocial working conditions only slightly increased the risk for sickness absence whereas favorable changes were unassociated with sickness absence. CONCLUSIONS: Changes in exposure to physical working conditions in particular are associated with subsequent sickness absence. Preventing an increase in exposure to both psychosocial and physical working conditions and promoting a decrease in exposure to physical working conditions likely helps reduce the risk of sickness absence.